Synthesis, Characterization, and Preliminary Evaluation of Biological Activity of 6-Mercaptopurine Heterocyclic Derivatives - Noor S. Hashim; Muthana S Farhan (Iraqi Journal of Pharmaceutical Sciences, 2025)
Bacterial infections are ongoing challenging due to resistance developed by infectious bacteria. So that many researches targeting designing new antibacterials are published annually. Heterocycles are important field in organic synthesis due to their biological activities. Because of their important and considerable pharmacological activities; 1,3-benzothiazole derivatives had received special attention. The purines nucleus are present in several compounds that possess a wide  range of  biological activities such as antiviral, antifungal, antitumor and antibacterial activities. Hybridization-combing two pharmacophores to form one molecule-is usual method in designing new drugs. The new derivatives of 6-mercaptopurine with 1,3-benzothiazole-2-amine were synthesized and characterized by TLC and spectroscopically by ATR-FTIR and 1HNMR and evaluated for their antibacterial activities. Disk diffusion method was used to evaluate the antibacterial activities of the new compounds.